Production of the 'Self' in the Digital Age - Ibrahim, Yasmin (Springer International Publishing, 2018)
This book investigates the relationship between the self and screen in the digital age, and examines how the notion of the self is re-negotiated and curated online. The chapters examine the production of the self in postmodernity through digital platforms by employing key concepts of ubiquity, the everyday, disembodiment and mortality. It locates self-production through ubiquitous imaging of the self and our environments with and through mobile technologies and in terms of its 'embeddedness' in our everyday lives. In this innovative text, Yasmin Ibrahim explores technology's co-location on our corporeal body, our notions of domesticity and banality, our renewed relationship with the screen and our enterprise with capital as well as the role of desire in the formation of the self. The result is a richly interdisciplinary volume that seeks to examine the formation of the self online, through its renewed negotiations with personalised technologies and with the emergence of social networking sites.